2010
DOI: 10.1103/physrevd.82.064004
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical shift condition for unequal mass black hole binaries

Abstract: Certain numerical frameworks used for the evolution of binary black holes make use of a gamma driver, which includes a damping factor. Such simulations typically use a constant value for damping. However, it has been found that very specific values of the damping factor are needed for the calculation of unequal mass binaries. We examine carefully the role this damping plays, and provide two explicit, non-constant forms for the damping to be used with mass-ratios further from one. Our analysis of the resultant … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…For the simulations with q > 4, we used the coordinate-dependent gauge term as described in Refs. [26] and [27]. For the q = 10 and q = 15 simulations, initial parameters in Ref.…”
Section: The Binary Black Hole Coalescence Waveformsmentioning
confidence: 99%
“…For the simulations with q > 4, we used the coordinate-dependent gauge term as described in Refs. [26] and [27]. For the q = 10 and q = 15 simulations, initial parameters in Ref.…”
Section: The Binary Black Hole Coalescence Waveformsmentioning
confidence: 99%
“…Recently it has been shown that a spatially varying η parameter may be helpful in the evolution of unequal mass binaries [41,42].…”
Section: Puncture Gauge Conditionsmentioning
confidence: 99%
“…In Sec. IV we discuss results for (42) and (43), because they are easier to obtain and the difference between those results and results obtained with (44) and (45) seems to be minor. Fig.…”
Section: Multiple Trumpetsmentioning
confidence: 95%
“…where we use (42) and (43) for the computation of the source terms in the right hand side of the equations. Additionally, we have set ∂ t K = ∂ tḡij = 0 and denoted the vector Laplacian by ∆ L , while (Lβ)…”
Section: Multiple Trumpetsmentioning
confidence: 99%
See 1 more Smart Citation